Treatment of Allergic Rhinitis: Anticholinergics, Glucocorticotherapy, Leukotriene Antagonists, Omalizumab and Specific-Allergen Immunotherapy - Jurado-Palomo, Jesus; Bobolea, Irina Diana; Gonzalez, Maria Teresa Belver; Moreno-Ancillo, Alvaro; Adrados, Ana Carmen Gil; Puebla, Jose Manuel Morales (IntechOpen, 2012)
None